Pembuatan Sistem Informasi Penerimaan Mahasiswa Baru (PMB) Politeknik Kampar Berbasis Web menggunakan PHP dan MySQL dengan Framework Codeigniter - Fitri (Jurnal Sains dan Ilmu Terapan, 2020)
The process of receiving new students at Politeknik Kampar is still manual, as the system becomes less maximum because of the less effective and efficient data processing as well as the possibility of missing or undivided prospective students ' data into Weakness factors due to the absence of a database system as well as the length of the data retrieval process when needed in a quick time. The solution is to create a new system based on Website. In the process of the design using the Unified Modeling Language (UML) method, as well as the implementation stage is done using the PHP programming language, phpMyAdmin for manages the databases in MySQL and the CodeIgniter framework. The conclusion of the final task is to have generated a new Student registration information system which is based on online, which is expected to overcome the problems in the new Student Registration information system at Kampar Polytechnic.